Economic evaluation of intravenous alteplase for stroke with the time of onset between 4.5 and 9 hours. (24th January 2022) - Chen, Jigang; Liang, Xin; Tong, Xin; Han, Mingyang; Ji, Linjin; Zhao, Songfeng; Hu, Zhiqiang; Liu, Aihua
Abstract : Background: A clinical trial proved the clinical effectiveness of perfusion imaging-guided intravenous thrombolysis with alteplase for patients with acute ischemic stroke (AIS) with the time of onset between 4.5 and 9 hours. This study aimed to assess the lifetime cost-effectiveness of alteplase versus placebo from the perspective of Chinese and United States (US) healthcare payers. Methods: A decision-analytic model was built to estimate lifetime costs and quality-adjusted life-years (QALYs) associated with alteplase or placebo. Model inputs were extracted from published sources. Incremental costs, incremental QALYs, and incremental cost-effectiveness ratio (ICER) were calculated to evaluate the base-case scenario. One-way and probabilistic sensitivity analysis were performed to evaluate uncertainty in the results. Results: In China, alteplase yielded an additional lifetime QALY of 0.126 with an additional cost of Chinese Yuan (¥) ¥9552 compared with placebo, and the ICER was ¥83 950 (US$12 157)/QALY. In the US, alteplase had a higher QALY (difference: 0.193) with a lower cost (difference: US$−2024) compared with placebo. In probabilistic sensitivity analyses, alteplase had a 42.54% to 78.3% probability of being cost-effective compared with placebo in China when the willingness-to-pay (WTP) threshold ranged from ¥72 447/QALY to ¥217 341/QALY. In the US, alteplase had a 93.47% to 93.57% probability of being cost-effective under the WTP threshold of US$100 000/QALY to US$150 000/QALY. These findings remained robust under one-way sensitivity analysis. Conclusion: For patients with AIS with a time of onset between 4.5 and 9 hours, perfusion imaging-guided intravenous alteplase was likely to be cost-effective in China and was cost-effective in the US when compared with placebo.